2021
DOI: 10.21203/rs.3.rs-272766/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuity of care and its determinants of routine maternal and newborn health visits in Nepal: Evidence from a nationally representative household survey

Abstract: Background Maternal and newborn health (MNH) is a priority health issue in Nepal, has high maternal and neonatal deaths. Maternal and neonatal deaths can be prevented through uptake of essential antenatal, intrapartum, and postnatal interventions received during routine MNH visits. Not all women, however, receive all recommended routine visits across the MNH Continuum of Care (CoC) in Nepal. This study examined the patterns and determinants of (dis)continuity of care across the MNH continuum. Methods The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The role of antenatal care is critical since pregnancy outcomes differ for women with and without prenatal care 52 . Among Indian women, antenatal and postnatal care decisions are influenced by their socio‐economic, cultural, and individual characteristics 53,54 and by the availability and accessibility of the health services 55 . It has been shown that the utiliztion of antenatal care services may result in the utilization of other maternal health‐related services such as institutional delivery and advice regarding post‐delivery complications 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of antenatal care is critical since pregnancy outcomes differ for women with and without prenatal care 52 . Among Indian women, antenatal and postnatal care decisions are influenced by their socio‐economic, cultural, and individual characteristics 53,54 and by the availability and accessibility of the health services 55 . It has been shown that the utiliztion of antenatal care services may result in the utilization of other maternal health‐related services such as institutional delivery and advice regarding post‐delivery complications 56 .…”
Section: Discussionmentioning
confidence: 99%
“…52 Among Indian women, antenatal and postnatal care decisions are influenced by their socio-economic, cultural, and individual characteristics 53,54 and by the availability and accessibility of the health services. 55 It has been shown that the utiliztion of antenatal care services may result in the utilization of other maternal health-related services such as institutional delivery and advice regarding post-delivery complications. 56 The clustering of child deaths can be greatly reduced by intervening with proper antenatal care coverage, as it influences the use of healthcare by women later on.…”
Section: Differentials In Observed Socioeconomic Characteristics Of F...mentioning
confidence: 99%
“…Low household incomes, high illiteracy, lack of awareness, and various cultural factors have been reported in studies from India and Pakistan as contributing to the low utilization of maternity facilities (Shariff & Singh 2002, Shaikh & Hatcher 2005. Similarly, research in Ethiopia has revealed that women's sociodemographic characteristics, cultural background, and proximity to healthcare facilities all play pivotal roles in determining the utilization of maternal health services (Mekonnen 2003).…”
Section: Introductionmentioning
confidence: 99%
“…6 Inadequate accessibility and under-utilization of healthcare services are major reasons for poor maternal health in the developing countries which in turn is due to many factors like low levels of income, illiteracy and ignorance, a bundle of traditional factors on one hand and substandard and inadequate public health services on the other. 4,7,8,9 This leads to increase in MMR and also child deaths.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several factors influence this model and determine the utilization of maternal health care services like socio-economic factors, availability, accessibility, affordability of health care services, women's autonomy in the household, women's knowledge, family attitudes, beliefs & culture. 4,8,9,14,15 This study was conducted to assess the utilization of maternal health care services and factors which influence them, in an urban slum; as this is the neglected region in an urban area.…”
Section: Introductionmentioning
confidence: 99%